Implementasi Pembinaan Pengawas dalam Meningkatkan Kinerja Profesional Guru Agama Katolik Melalui Supervisi Kinerja di Sekolah Dasar Binaan Kota Mataram - Maksimilianus Naben (Universitas Pendidikan Mandalika, 2022)
This study aims to improve the professional performance of Catholic religious education teachers through supervising the performance of supervisors in the primary schools assisted by the city of Mataram. This research method uses classroom action research. The subjects of this study were 17 teachers of Catholic religious education at the targeted elementary schools in the sub-districts of Cakranegara, Mataram and Ampenan. Data collection techniques using observation and questionnaires. Meanwhile, data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of this study are (1) Supervising development in an effort to improve the performance of Catholic religious education teachers through performance supervision shows an increase in each cycle; (2) Activities in coaching activities show that all Catholic religious teachers can improve their performance well in every aspect. (3) The performance improvement of Catholic religious education teachers by supervisors through this performance supervision shows an increase in each cycle. (4) The activities of Catholic religious education teachers show that coaching activities through performance supervision are beneficial and can help Catholic religious education teachers to more easily understand their roles and functions as religious education teachers, so that the performance of Catholic religious education teachers can increase.